KAJIAN PENGARUH VARIASI KONSENTRASI ASAM SITRAT TERHADAP KEKUATAN GEL PRODUK GELATIN KULIT AYAM BROILER DIKAITKAN DENGAN POLA PROTEINNYA - Hardikawati, Tutut; Puspawati, Ni Made; Ratnayani, Ketut (Jurnal Kimia (Journal of Chemistry); Vol. 10, No. 1 Januari 2016, 2016)
Gelatin is a biopolymer that can be generated from partially hydrolysis of collagen tissue. Extraction of gelatin consists of pretreatment and thermal extraction steps. Pretreatment process used sodium hydroxide to remove non collagen protein in matrix sample, sulfuric acid to demineralize, and citric acid to hydrolyse. The aim of this research was to study the effect of variation in concentrations of citric acid used in hydrolysis process on the gel strength and protein profile of gelatin products extracted from broiler chicken skin.  The variation of the concentration citric acid used was 0.7 % (GA); 1.5% (GB); and 3.0% b/v (GC) respectively. The gel strength was measured using CT3 Texture Analyzer and protein profile of gelatin product was analyzed by SDS-PAGE method . The result showed that variation in concentration of citric acid used in the pretreatment process affected the gel strength and protein profile of gelatin product. Increasing the concentration of citric acid used in pretreatment process decreased the gel strength and molecular weight of gelatin product. Gel strength of each gelatin product was 265.81 g bloom for GA ; 196.05 g bloom for GB (1.5%), and 35.32 g bloom for GC (3.0 %) respectively. The electropherogram of both GA (0.7%) and GB (1.5%) revealed similar pattern of protein bands but the thickness of each bands was different.  On the other hands, GC (3.0%) did not show any protein bands on the eletropherogram. The best gelatin product obtained in this experiment was found by using 0.7 % b/v citric acid (GA) in the pretreatment process. The gelatin product (GA) had characteristics as follows: yield 15.73%; moisture 7.30%; ash 0.51%; protein content 97.95%; fat content 0.62%; gel strength 265. 81 g bloom and thicker protein bands than others.
Keywords: broiler chicken skin, gelatin, citric acid, protein profile, and gel strength